PROGNOSIS FOR DISASTERS CAUSED BY ACCIDENTS IN THE REGION OF VARNA BULGARIA - H. Romanova; N. Radeva; I. Marinova; M. Marinov; B. Bojchev; K. Mirtchev; Radko Z. Radev (Peytchinski Publishing, 2011)
Disastrous situations result from the action of natural and technological (anthropogenic) factors. The technological disasters become more common due to the considerable progress in the field of modern industrial technologies. They represent a permanently threatening potential danger for the world as a whole, for Bulgaria and for the region of Varna as well. The production capacities and the stored and used industrial toxic substances along with the natural-geographic peculiarities contributing to the polluted territory after accidents in the region of Varna were analyzed. A flexible and rapidly adapting organization of medical service in case of disasters was created.